The Impact of Hospital Administration Service Quality on Patient Satisfaction of Health Insurance Agencies: A Cross-Sectional Study - Pasaribu, Usrawati; Harahap, Herawati; Lastari, Asdi; Permayasa, Nayodi; J. Hadi, Anto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Service quality is very closely related to patient satisfaction. One of the reasons for the progress of a hospital is influenced by its attitude or nature or the hospital's ability to serve its patients. This study aims to analyze the impact of the quality of hospital administration services on patient satisfaction of health insurance agencies at the Outpatient Installation of Pintu Padang Regional General Hospital, South Tapanuli Regency. Methods: Type of observational research with a cross-sectional study design. This research was carried out at the Outpatient Installation of the Pintu Padang Regional General Hospital. The population and sample are all patients who received treatment in November 2024, as many as 135 people. Data collection was carried out using a research questionnaire. Sampling techniques with exhaustive sampling and data analysis using chi-square and logistic regression. Results: This study proved that the speed of administrative services (p=0.001), friendliness, and attitude of administrative staff (p=0.001) affected patient satisfaction. Conclusion: The quality of administrative services in hospitals has a significant effect on BPJS patient satisfaction, especially in terms of speed, clarity, and staff friendliness. It is recommended that hospitals improve the efficiency of administration and staff training. Subsequent research should involve a broader sample and consider other factors that affect patient satisfaction.